PRODUCTION OF METHYL ESTER FROM VARIOUS COCONUT OILS - Ardi Kurniawan Makalalag (Balai Riset Dan Standardisasi Industri Manado, 2018)
Production of methyl ester from various coconut oils had been studied. This study aimed to determine optimal method for methyl esther production based on free fatty acid content and methyl ester yield. This study used crude coconut oil (CCO) which was processed from smoked copra, neutralized coconut oil and VCO whose phenolic compounds had been extracted, as raw materials Descriptive study of esterification process was carried out using methanol and NaOH catalyst at temperature of 60 oC for 3 hours. The results showed thet free fatty acid content of crude coconut oil, neutralized coconut oil, and VCO whose phenolic compounds had been extracted were 4.28%, 1.14%, and 0.17% respectively. Methyl esters produced from the three materials ranged from 61.5-65.5% with acid numbers 0.64-0.72 mgKOH / gr, saponification number 261.50 - 270.57 mg / g, and crude glycerol yield 17.75-22.75%. Chromatogram (graph) of fatty acids in methyl esters showed relatively similar pattern. Coconut oil and VCO whose phenolic compounds had been extracted could be processed into methyl esters by transesterification using methanol and NaOH catalysts.Keywords: Coconut oil, free fatty acid, methyl ester.